Assessment of efficiency of Greek airports - Psaraki-Kalouptsidi, V.; Kalakou, S. (Journal of Airport Management, 2011)
This paper assesses the efficiency of Greek airports using data envelopment analysis (DEA). Appropriate inputs and outputs describing primary airport functions are identified. First, the landside and airside infrastructure of the airports are evaluated in terms of the movements served during the period 2004–07. In contrast to previous studies, special emphasis is focused on passenger building and its potential to serve passenger traffic. Then economic efficiency is assessed. The paper reports on pure technical efficiency, scale efficiency, airport potential and peer airports.